Desain Sistem Pembangkit Listrik Optimal On-Grid Tenaga Surya Dan Bayu Menggunakan Software Homer Di Kecamatan Asakota, Kota Bima. - Fadhillah Umar Rahman; Citra Putri Maharani; Nur Habiiburrahman; Much. Dede Pratama; Agung Budi Muljono (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING, INFORMATION TECHNOLOGY, CONTROL ENGINEERING, AND ROBOTIC), 2024)
Indonesia is currently facing a complex energy crisis characterized by high dependence on fossil fuels such as coal, petroleum and natural gas. This crisis has an impact on energy security, public health and environmental sustainability. In Bima City, NTB, the energy crisis is clearly visible with frequent power outages and high prices of fossil fuels. However, Bima City has quite large potential to develop renewable energy, especially solar and wind energy. This research aims to determine the effect of solar radiation and wind speed on electricity production at solar and wind power plants in the Asakota District and to design an optimal on-grid power generation system using HOMER software. The simulation results show that the correct system development planning with a total annual load of 2424.25 kWh/year, namely with the NPC value, the system costs IDR 9,993,555,000.00 which is capable of producing electrical energy that can be sold at a price of IDR 431.37. /kWh with operational costs of IDR 390,296,400.00. The energy produced by the PV Panel is 643,009 kWh/yr and the Agin Turbine is 632,357 kWh/yr and the excess energy for tertiary needs is 142,014 kWh/year. The study also provides insight into the benefits of solar and wind energy and the use of HOMER software for planning power generation systems.